(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
In the recent development of world linguistics, the study of the comparative typological, linguocognitive, lingvopragmatic, lingvocultural and lingvopsychological features of communication, speech, structural research and neuropsycholinguistics has become increasingly relevant. From time immemorial, philosophers, linguists, sociologists, psychologists, and even physicians have been interested in the problems of language personality and speech culture. This article discusses the role and importance of communicative speech in integrating a linguistic person into a charismatic person through speech.